2007
DOI: 10.1038/sj.npp.1301463
|View full text |Cite
|
Sign up to set email alerts
|

Acute Amphetamine Exposure Selectively Desensitizes κ-Opioid Receptors in the Nucleus Accumbens

Abstract: In the present study, we investigated the effects of psychostimulant exposure on k-opioid peptide (KOP) receptor signaling in the rat mesolimbic system. A single subcutaneous (s.c.) injection of amphetamine (2.5 mg/kg) reduced the KOP receptor-mediated inhibition of glutamate release in the nucleus accumbens shell, as a consequence of KOP receptor desensitization. This effect was blocked by dopamine (DA) receptor antagonists or the nonselective opioid antagonist, naltrexone (1 mg/kg, s.c.), and mimicked by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Basal adenylyl cyclase activity in the saline-treated controls for the various nicotine groups was not different, and values have been pooled for presentation purposes. N=12 animals/ group *P<0.05 compared with saline basal; **P<0.05 compared with respective saline basal Recently, Xia et al (2008) reported that administration of a single dose of amphetamine desensitizes KOPrs in the NAc through heightened dynorphin release, a mechanism analogous to the one we posit as underlying KOPr desensitization during nicotine withdrawal. Both membrane and autoradiography binding studies showed that the density of KOPrs was not altered in the striatum and its sub-regions following chronic nicotine administration and withdrawal.…”
Section: Discussionmentioning
confidence: 75%
“…Basal adenylyl cyclase activity in the saline-treated controls for the various nicotine groups was not different, and values have been pooled for presentation purposes. N=12 animals/ group *P<0.05 compared with saline basal; **P<0.05 compared with respective saline basal Recently, Xia et al (2008) reported that administration of a single dose of amphetamine desensitizes KOPrs in the NAc through heightened dynorphin release, a mechanism analogous to the one we posit as underlying KOPr desensitization during nicotine withdrawal. Both membrane and autoradiography binding studies showed that the density of KOPrs was not altered in the striatum and its sub-regions following chronic nicotine administration and withdrawal.…”
Section: Discussionmentioning
confidence: 75%
“…Although not physiologically verified at this point, these findings are consistent with a large body of literature describing compensatory changes in neuropeptide and G-protein expression and function in response to manipulations of dopamine signaling within the mesolimbic system. Dopamine depletion results in decreased dynorphin expression (Gerfen, 2000), whereas the dopamine-releasing drug amphetamine stimulates transcription of dynorphin (Cole et al, 1995) and increases dynorphin release, which subsequently desensitizes KORs (Xia et al, 2008). The mechanism underlying KOR agonist-mediated KOR desensitization is not fully understood, but may involve downregulation of G-proteins such as Gi2.…”
Section: Discussionmentioning
confidence: 98%
“…That is, dynorphin peptides are transported to recurrent collateral axons within the NAc in order to decrease DA or glutamate transmitter release via presynaptic κ-opioid receptors (Steiner and Gerfen 1993). κ-opioid receptors also desensitize in response to high levels of dynorphin, including those induced by a single injection of amphetamine, subsequently increasing DA signaling on MSNs in vivo (Xia et al 2008). Chronically elevated DA levels across the daily 16 hour ethanol exposure that occurs with CIE (for 4 weeks) may induce repeated κ-opioid receptor desensitization, resulting in a subsequent upregulation of κ-opioid receptors in a manner similar to nicotine-induced nACh receptor upregulation (Fenster et al 1999).…”
Section: Discussionmentioning
confidence: 99%